2016
DOI: 10.1016/j.actbio.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-based intranasal delivery of lipopeptide vaccine candidates against group A streptococcus

Abstract: Group A streptococcus, causing rheumatic heart diseases, kills approximately half a million people annually. There is no vaccine available against the infection. Mucosal immunity is vital in ensuring an individual is protected as this gram positive bacteria initially colonizes at the throat. Herein, we demonstrated that lipopeptides entrapped by liposomes induced both mucosal and systemic immunity. High levels of antibody (IgA and IgG) titres were detected even five months post immunization and lead vaccine ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 38 publications
1
61
0
Order By: Relevance
“…An indirect bactericidal assay indicated that serum antibodies produced in mice immunized with NP-1 were effective not only against the M1 GAS strain, but also against a variety of clinical isolates ( Figure 5D). Overall, NP-1, even at low antigen concentration compared to previous reports [30,[51][52][53], induced high IgA and opsonic IgG antibody titers and showed protection against GAS infection.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…An indirect bactericidal assay indicated that serum antibodies produced in mice immunized with NP-1 were effective not only against the M1 GAS strain, but also against a variety of clinical isolates ( Figure 5D). Overall, NP-1, even at low antigen concentration compared to previous reports [30,[51][52][53], induced high IgA and opsonic IgG antibody titers and showed protection against GAS infection.…”
Section: Discussionmentioning
confidence: 45%
“…To determine J8-specific IgG and IgA antibody titers, enzyme-linked immunosorbent assays (ELISA) were performed [30]. Flat bottom 96-well plates were coated with J8 peptide (5 µg/well) and blocked with 5% skim milk.…”
Section: Determination Of Antibody Titersmentioning
confidence: 99%
“…Previous liposomal research involved vaccine construction using cationic liposomes with peptide antigens and the use of linked ‘universal’ T-cell epitope peptides to induce T-cell help3435. These are useful approaches but lack the utility of the Peptide-Lipo-DT approach where additional B-cell peptide epitopes can be readily displayed on the liposomal surface and do not require chemical conjugation to a T-cell peptide epitope.…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect was observed when lipids were used to anchor peptides to liposomes. 24,25 Taken together, the physicochemical properties of liposomes 8Qm-L and 8Qm-D-L were only slightly different.…”
Section: Synthesis and Characterization Of 8qm-d And 8qm-d-lmentioning
confidence: 98%
“…Importantly, the combination of a liposomal delivery system with the conjugation strategy improved immune response in a synergistic manner. 24 Here we examined whether this strategy can also be applied to polymer-based conjugates designed to induce cellular immune responses. Thus, C57Bl/6 female mice were inoculated subcutaneously in the flank with 2 x10 5 TC-1 cells/mouse on day 0, then mice were immunized with 8Qm-D, 8Qm-L, 8Qm-D-L, and controls (PBS, 8Qm + IFA) on day 7.…”
Section: In Vivo Tumor Treatmentmentioning
confidence: 99%